PREMATURE BABIES WITH FETAL GROWTH RESTRICTION: A MODERN VIEW OF THE PROBLEM - Yuditskiy, Anton Demitrievich (Mother and Baby in Kuzbass, 2026)
Fetal growth restriction (FGR) is an interdisciplinary problem attracting the attention of obstetricians, neonatologists, and pediatricians. Priority research areas include improving diagnostic efficiency, optimizing perinatal monitoring, and choosing the optimal timing of delivery, which determine the nature of potential adverse effects both in newborns and later in life.The aim of the research – to analyze and summarize current data from Russian and international literature on intrauterine growth restriction in preterm infants, including terminology, epidemiology, etiopathogenesis, perinatal outcomes, and neonatal morbidity patterns in various clinical forms of FGR.Material and methods. Analyzed scientific publications in Russian and international peer-reviewed journals, as well as guidelines from international expert organizations (WHO, FIGO) and consensus documents (Delphi consensus, COSNEON). The literature search was conducted using the following keywords: intrauterine growth restriction, fetal growth restriction, small-for-gestational age, premature infants, neonatal morbidity, perinatal outcomes.Results. An analysis of neonatal morbidity in early-onset IUGR demonstrates a high incidence of respiratory distress syndrome (up to 36%), bronchopulmonary dysplasia (up to 43%), necrotizing enterocolitis (up to 11-22%), retinopathy of prematurity (up to 29%), and neonatal sepsis (up to 64%). IUGR was found to be an independent risk factor for psychomotor developmental disorders in early-onset premature infants.Conclusion. The health status and range of diseases in premature infants with FGR depend on a wide range of causes and risk factors. Given the inconsistency of the obtained results, further study and development of scientifically based approaches to predicting and preventing the most significant pathology associated with fetal growth restriction in preterm infants is relevant.
Keywords: fetal growth restriction; preterm infants; neonatal morbidity; small-for-gestational age; perinatal outcomes